DINAMIKA IJTIHAD KOLEKTIF DAN PENGEMBANGAN SUMBER HUKUM ISLAM ERA KHULAFA’ AL-RĀSYIDĪN - Ahmad Zulkifli Affandi; Lomba Sultan; Azman Arsyad (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2025)
This study aims to explore the legislative function of the sahabah (companions of the Prophet), the authority of fatwa, the use of legal sources, and the long-term impact on the structure of Islamic law during the Khulafā’ al-Rāsyidīn period. Employing a qualitative, normative-juridical approach through library research, the analysis is based on primary and secondary sources such as the Qur’an, Hadith, classical Islamic legal texts, and relevant scholarly articles. The findings reveal that the collective ijtihad and fatwa practices of the sahabah were innovative responses to unprecedented legal challenges following the Prophet’s death, ensuring the continuity and adaptability of Islamic law in a rapidly changing socio-political landscape. The research highlights the pivotal role of collective authority and consultation (shura) in the legislative process, which laid the groundwork for the emergence of Islamic legal schools (mazhab). This study’s novelty lies in its comprehensive analysis of the collective dimension of fatwa authority and its long-term influence on Islamic legal structures, which has been underexplored in normative literature. The results suggest that the adaptive model of legislation and fatwa from this era can inform contemporary Islamic legal reforms, and further research is recommended to deepen understanding of shura mechanisms and fatwa authority as models for modern Islamic jurisprudence.